Investigation of Turkish and Turkmenistanian Students’ Approaches towards Environmental Ethics and Their Levels of Naturalistic Intelligence - Sibel Gurbuzoglu-Yalmanci; Solmaz Aydin-Beytur (Journal of Education in Science, Environment and Health)
The purpose of this study is to compare the attitudes of Turkmenistanian and Turkish university students towards environmental ethics approaches and their naturalistic intelligence (NI) field. In addition, it was investigated whether there is a gender difference in environmental ethics levels in both countries students’. Environmental Ethics Attitude Scale (EEAS) and Multiple Intelligence Areas Inventory were applied to the students. A total of 172 Turkish and 103 Turkmenistanian university students participated. A significant difference between the mean scores of Turkish and Turkmenistanian was observed in all four categories of environmental ethics [Anthropocentric, Ecocentric, Ecofeminism, Teocentric]. The analyses conducted to test gender differences showed that there was not a significant difference between male and female Turkmenistanian students’ EAA mean scores. Comparison of NI levels of students from both countries suggested that Turkish students’ NI levels were “developed” and Turkmenistanian students’ NI levels were “moderately developed”. The research findings were considered for both countries students’.